PD1Hi CD8+ T cells correlate with exhausted signature and poor clinical outcome in hepatocellular carcinoma. Issue 1 (29th November 2019) - Ma, Jiaqiang; Zheng, Bohao; Goswami, Shyamal; Meng, Lu; Zhang, Dandan; Cao, Chunmei; Li, Teng; Zhu, Fangming; Ma, Lijie; Zhang, Zhao; Zhang, Shuhao; Duan, Meng; et al.
Abstract : Background: CD8 + T cells differentiate into exhausted status within tumors, including hepatocellular carcinoma (HCC), which constitutes a solid barrier to effective anti-tumor immunity. A detailed characterization of exhausted T cells and their prognostic value in HCC is lacking. Methods: We collected fresh tumor tissues with adjacent non-tumor liver tissues and blood specimens of 56 HCC patients, as well as archived samples from two independent cohorts of HCC patients ( n  = 358 and n  = 254), who underwent surgical resection. Flow cytometry and multiplex immunostaining were used to characterize CD8 + T cells. Patient prognosis was evaluated by Kaplan-Meier analysis and Cox regression analysis. Results: CD8 + T cells were classified into three distinct subpopulations: PD1 Hi, PD1 Int and PD1 − . PD1 Hi CD8 + T cells were significantly enriched in tumor compared to adjacent non-tumor liver tissues. PD1 Hi CD8 + T cells highly expressed exhaustion-related inhibitory receptors (TIM3, CTLA-4, etc.) and transcription factors (Eomes, BATF, etc.). In addition, PD1 Hi CD8 + T cells expressed low levels of cytotoxic molecules and displayed a compromised capacity to produce pro-inflammatory cytokines while the expression of anti-inflammatory IL-10 was up-regulated following mitotic stimulation. Furthermore, PD1 Hi CD8 + T cells shared features with tissue resident memory T cells and were also characterized in an aberrantly activated status with an apoptosis-prone potential. In two independent cohorts of HCC patients ( n  = 358 and n  = 254), we demonstrated that PD1 Hi or TIM3 + PD1 Hi CD8 + T cells were significantly correlated with poor prognosis, and the latter was positioned in close proximity to PD-L1 + tumor associated macrophages. Conclusion: The current study unveils the unique features of PD1 Hi CD8 + exhausted T cells in HCC, and also suggests that exhausted T cells could act as a biomarker to select the most care-demanding patients for tailored therapies.